2021
DOI: 10.1002/joc.6977
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication: CMIP6 does not suggest any atmospheric blocking increase in summer over Greenland by 2100

Abstract: The Greenland blocking index (GBI), an indicator of the synoptic‐scale circulation over Greenland, has been anomalously positive during most summers since the late 1990s. Such changes in atmospheric circulation, favouring anticyclonic conditions, have led to an increase in Greenland summer temperatures, a decrease in cloud cover and larger surface melt. The GBI is therefore a key indicator of melting and surface mass balance variability over the Greenland ice sheet. However, the models of fifth phase of the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 41 publications
2
33
1
Order By: Relevance
“…Fully coupled CMIP6 simulations (i.e., with an active ocean and sea ice component) show decreases in blocking over Greenland (Delhasse et al 2021), in opposition to our results presented here. We hypothesize that cooling of sea surface temperatures in the North Atlantic (Sellevold and Vizcaino 2020), due to the projected slowdown of the North Atlantic Meridional Overturning Circulation in the fully coupled models, causes the decrease in Greenland blocking.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Fully coupled CMIP6 simulations (i.e., with an active ocean and sea ice component) show decreases in blocking over Greenland (Delhasse et al 2021), in opposition to our results presented here. We hypothesize that cooling of sea surface temperatures in the North Atlantic (Sellevold and Vizcaino 2020), due to the projected slowdown of the North Atlantic Meridional Overturning Circulation in the fully coupled models, causes the decrease in Greenland blocking.…”
Section: Discussioncontrasting
confidence: 99%
“…7 b), as the winds affect the amount of moisture transfer over the ice sheet. Further, this circulation anomaly is similar to the circulation anomaly associated with the Greenland blocking index (Davini et al 2012 ; Hanna et al 2015 , 2018 ). However, the present-day GBI-related anomaly is approximately 6 stronger than the circulation anomaly found here (Hanna et al 2016 ).…”
Section: Resultssupporting
confidence: 76%
“…S1b in the Supplement), once integrated over the whole ice sheet (see Table S1 in the Supplement), these anomalies compensate for each other and the SMB components as well as the solar radiation compare very well with the ones from MAR forced by ERA5. Furthermore, Delhasse et al (2021) showed that CMIP6 models do not suggest any change in general circulation in summer. This suggests that the pattern of the present-day runoff anomalies should remain unchanged through the MAR simulation and then that the excess of runoff along the south-west margin should continue to compensate for the lack of runoff in the north-east.…”
Section: Modelsmentioning
confidence: 99%
“…However, the total yearly melt rates match well with those of MAR over the period 1958-2019 and on this timescale the skill of the model is comparable to the dEBM (Krebs-Kanzow et al, 2020). The exception of the extreme melt in the years 2012 and 2019, where dEBM-simple clearly underestimates melt rates, are related to changes in cloud cover or blocking events (Delhasse et al, 2021;Hanna et al, 2014;Hofer et al, 2017), which are not captured by the parameterization of the transmissivity of the atmosphere.…”
Section: Implementation and Validationmentioning
confidence: 59%